2015
DOI: 10.1039/c5ra06763d
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy for simultaneous determination of 4-aminophenol, uric acid and nitrite based on a graphene/hydroxyapatite composite modified glassy carbon electrode

Abstract: A novel electrochemical sensor has been fabricated based on a graphene/hydroxyapatite composite modified GCE for the selective and simultaneous detection of 4-aminophenol, uric acid and nitrite ions (NO2−) by voltammetric method for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…In their study, the fabricated GNs-HA modified glassy carbon electrode (GCE) exhibited excellent electrocatalytic activity in the redox process of luteolin compared with GNs-GCE electrode, attributing to the enhanced electron transfer and electrocatalysis toward luteolin. In another case, an electrochemical sensor based on GO-HA composites-modified GCE was fabricated for simultaneous determination of 4-aminophenol (4-AP), uric acid (UA), and nitrite ions (NO 2− ) by cyclic voltammetry (CV) and square wave voltammetry measurements [89]. They found that the formed GO-HA nanocomposite exhibited synergistic effects with high sensitivity, low detection limits, good stability, and high reproducibility.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…In their study, the fabricated GNs-HA modified glassy carbon electrode (GCE) exhibited excellent electrocatalytic activity in the redox process of luteolin compared with GNs-GCE electrode, attributing to the enhanced electron transfer and electrocatalysis toward luteolin. In another case, an electrochemical sensor based on GO-HA composites-modified GCE was fabricated for simultaneous determination of 4-aminophenol (4-AP), uric acid (UA), and nitrite ions (NO 2− ) by cyclic voltammetry (CV) and square wave voltammetry measurements [89]. They found that the formed GO-HA nanocomposite exhibited synergistic effects with high sensitivity, low detection limits, good stability, and high reproducibility.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“… The number of publications on Graphene-based HA composites from year 2009–2016 (2009 [ 16 ], 2011 [ [17] , [18] , [19] ], 2012 [ [20] , [21] , [22] , [23] , [24] ], 2013 [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], 2014 [ [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], 2015 [ [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ...…”
Section: Introductionunclassified
“…It can produce methaemoglobin, responsible for the anemic condition, nitrite reacts with various amines and amides to form N-nitrosamines which cause stomach cancer. [7] Researchers in recent years have focused on the development of new techniques such as ion chromatography, gas chromatography, HPLC, chemiluminescence, capillary electrophoresis, spectrophotometric, mass spectrophotometric, and electrochemical methods. [8] Among the above methods, comprehensive attention has been paid to the electrochemical methods due to their quick response, easy and controlled operation, high sensitivity, and extremely high selectivity.…”
Section: Introductionmentioning
confidence: 99%